Cognitive health of older persons in longitudinal ageing cohort studies - Ng, Tze Pin (Penerbit Universiti Kebangsaan Malaysia, 2016)
Dementia poses a major global burden of care to society and health systems in ageing populations. The majority (over 60%) of persons with dementia in the world are found in Asia and developing countries with rapid rates of population ageing. Improving and maintaining the cognitive health of older persons is vital to national strategies for dementia prevention. Increasing numbers of population-based ageing cohort studies in the past decade have provided a better understanding of the factors that contribute to cognitive function and decline in old age. The roles of major demographic, psychosocial, lifestyle, behavioral and cardiovascular risk factors contributing to cognitive health were discussed using examples from the Singapore Longitudinal Ageing Studies. They include socio-demographic factors, particularly education and marital status, leisure time activity such as physical activity, social engagement and mental activities, psychological factors such as depression, cardiovascular and metabolic risk factors: obesity, diabetes, hypertension and dyslipidemia, and the metabolic syndrome, under-nutrition, low albumin, low hemoglobin, nutritional factors such as blood folate, B12 and homocysteine, omega-3 poly-unsaturated fatty acids, tea drinking and curcumin-rich turmeric in curry meals. These factors are found to be associated variously with cognitive functions (memory and learning, language, visuospatial, attention and information processing speed), rates of cognitive impairment and cognitive decline, or increased risk of developing MCI and progression to dementia.